Sedimentation Analysis at Cariang Weir in Sumedang District using Mike 21 Software - Sudirman, Sudirman; Mulyawati, Fauzia; Sudarsono, Ignatius (Universitas Negeri Padang, 2024)
Sedimentation is the deposition of material carried by water media. The occurrence of sedimentation disrupts river flow, leading to increased susceptibility to flooding and drought during dry seasons. The impact of sedimentation causes riverbed siltation, reducing the river's capacity from its natural state. The Cariang Dam, located in Ujung Jaya Village, Ujung Jaya District, Sumedang Regency, is experiencing sedimentation issues. This has resulted in siltation and a decrease in the river's capacity at the dam site. In light of these issues, the researcher is interested in analyzing sedimentation at the Cariang Dam area. This analysis aims to determine the volume and height of sedimentation occurring annually. Based on the analysis conducted, the sedimentation height per day is found to be 0.7 centimeters, amounting to 23 centimeters per month and 276 centimeters annually.